The epidemiology of conjunctival squamous cell carcinoma in Uganda. - Newton, R; Ziegler, J; Ateenyi-Agaba, C; Bousarghin, L; Casabonne, D; Beral, V; Mbidde, E; Carpenter, L; Reeves, G; Parkin, D; Wabinga, H; Mbulaiteye, S; et al. (2002)
As part of a larger investigation of cancer in Uganda, we conducted a case-control study of conjunctival squamous cell carcinoma in adults presenting at hospitals in Kampala. Participants were interviewed about social and lifestyle factors and had blood tested for antibodies to HIV, KSHV and HPV-16, -18 and -45. The odds of each factor among 60 people with conjunctival cancer was compared to that among 1214 controls with other cancer sites or types, using odds ratios, estimated with unconditional logistic regression. Conjunctival cancer was associated with HIV infection (OR 10.1, 95% confidence intervals [CI] 5.2-19.4; P<0.001), and was less common in those with a higher personal income (OR=0.4, 95% CI 0.3-0.7; P<0.001)[corrected]. The risk of conjunctival cancer increased with increasing time spent in cultivation and therefore in direct sunlight (chi2 trend=3.9, P=0.05), but decreased with decreasing age at leaving home (chi2 trend=3.9, P=0.05), perhaps reflecting less exposure to sunlight consequent to working in towns, although both results were of borderline statistical significance. To reduce confounding, sexual and reproductive variables were examined among HIV seropositive individuals only. Cases were more likely than controls to report that they had given or received gifts for sex (OR 3.5, 95% CI 1.2-10.4; P=0.03), but this may have been a chance finding as no other sexual or reproductive variable was associated with conjunctival cancer, including the number of self-reported lifetime sexual partners (P=0.4). The seroprevalence of antibodies against HPV-18 and -45 was too low to make reliable conclusions. The presence of anti-HPV-16 antibodies was not significantly associated with squamous cell carcinoma of the conjunctiva (OR 1.5, 95% CI 0.5-4.3; P=0.5) and nor were anti-KSHV antibodies (OR 0.9, 95% CI 0.4-2.1; P=0.8). The 10-fold increased risk of conjunctival cancer in HIV infected individuals is similar to results from other studies. The role of other oncogenic viral infections is unclear.